The outcomes of cardiopulmonary resuscitation and their predictors during the coronavirus 2019 pandemic in Iran - Afshin Goodarzi; Alireza Abdi; Hooman Ghasemi; Niloofar Darvishi; Rostam Jalali (BMC Emergency Medicine, 2023)
Abstract Background Coronavirus disease 2019 (COVID-19) can negatively affect different healthcare-related outcomes. Nonetheless, there is limited information about its effects on different healthcare-related outcomes. This study aimed at evaluating the outcomes of cardiopulmonary resuscitation (CPR) and their predictors during the COVID-19 pandemic in Iran. Methods This cross-sectional study was conducted on 1253 patients who had undergone CPR in the emergency wards of teaching hospitals in the west of Iran from the beginning of the first wave to the end of the third epidemic wave of COVID-19 in Iran, between February 20, 2020, and January 20, 2021. Data were collected using the National CPR Documentation Forms developed based on the Utstein Style and routinely used for all patients with cardiac arrest (CA). The SPSS (v. 20.0) program was used to analyze the data through the Chi-square, Fisher’s exact, and Mann-Whitney U tests and logistic regression analysis. Results Participants’ age mean was 64.62 ± 17.54 years. Age mean among participants with COVID-19 was eight years more than other participants. Most participants were male (64.09%) and had at least one underlying disease (64.99%). The total rates of the return of spontaneous circulation (ROSC) and CPR–discharge survival were respectively 15.3% and 3.8% among all participants, 20.25% and 5.17% among participants without COVID-19, and 8.96% and 2.04% among participants with COVID-19. The significant predictors of ROSC were age, affliction by COVID-19, affliction by underlying diseases, baseline rhythm, delay in epinephrine administration, and epinephrine administration time interval, while the significant predictors of CPR–discharge survival were age and baseline rhythm. Conclusions The total rates of ROSC and CPR–discharge survival were respectively 15.3% and 3.8% among all participants. The rates of ROSC and CPR to discharge survival among patients without COVID-19 are respectively 2.26 and 2.53 times more than the rates among patients with COVID-19.